Hutchinson-Gilford Progeria Syndrome: A Rare Genetic Disorder. (30th October 2013) - Panigrahi, Rajat G.; Panigrahi, Antarmayee; Vijayakumar, Poornima; Choudhury, Priyadarshini; Bhuyan, Sanat K.; Bhuyan, Ruchi; Maragathavalli, G.; Pati, Abhishek Ranjan
Abstract : Hutchinson-Gilford progeria syndrome (HGPS) is a rare pediatric genetic syndrome with incidence of one per eight million live births. The disorder is characterised by premature aging, generally leading to death at approximately 13.4 years of age. This is a follow-up study of a 9-year-old male with clinical and radiographic features highly suggestive of HGPS and presented here with description of differential diagnosis and dental consideration. This is the first case report of HGPS which showed pectus carinatum structure of chest.